The Influence of Online Customer Review, Online Customer Experience, Brand Trust on Purchase Decisions Through TikTok Affiliate Content - Syarafah, Nur Indah; Hariyanto, Didik (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
The development of digital technology has been able to change the lifestyle of social society, especially in the marketing process which was originally conventional to digital or online. This change is supported by the emergence of affiliate programs that are useful for expanding marketing reach and increasing the effectiveness of marketing costs, by providing mutually beneficial benefits between sellers, buyers, and TikTok Affiliate content creators. The purpose of this study is to determine the effect of Online Customer Review, Online Customer Experience and Brand Trust on Purchasing Decisions through Tiktok Affiliate content for students in Sidoarjo Regency. This study uses a quantitative method with a descriptive approach. Sampling uses probability sampling techniques by distributing questionnaires through the help of Google Form. The sample used in this study amounted to 155 respondents. The data analysis technique in this study uses SEM-PLS analysis with the help of SmartPLS software. The results of the study show that Online Customer Review and Online Customer Experience have a positive and significant influence on Purchasing Decisions through TikTok Affiliate content. While Brand Trust has no influence and is not significant on Purchasing Decisions through TikTok Affiliate content. The main factors influencing purchasing decisions in this study are the quality and effectiveness of TikTok Affiliate content, which significantly affects Online Customer Review and Online Customer Experience.